Supporting couples with polycystic kidney disease in a medically assisted reproduction process - Daniela Zuccarello; Claudia Livi; Valentina Zicaro; Sara Communci; Ludovica Picchetta (AboutScience Srl, 2024)
Preimplantation diagnosis process for couples with polycystic kidney disease involves several steps: genetic and gynecological counseling, in vitro fertilization (IVF/ICSI), embryo biopsy, genetic analysis, selection of healthy embryos and implantation. The importance of preimplantation diagnosis for couples affected by polycystic kidney disease (PKD) lies in several key factors:   Prevention of Inherited Disease: PKD is a genetic disorder with a high likelihood of being passed from parent to offspring. Preimplantation diagnosis offers couples the opportunity to identify and avoid passing on the disease to their children. Family Planning Options: By undergoing preimplantation diagnosis, couples can make better decisions about their family planning options. They can select embryos that do not carry the PKD gene mutation and reduce the risk of having a child affected by the disease. Emotional Burden Reduction: PKD can lead to significant emotional burdens for affected individuals and their families. Preimplantation diagnosis provides a proactive approach to avoiding these burdens by preventing the transmission of the disease to next generations. Enhanced Reproductive Choices: With preimplantation diagnosis, couples have greater control over their reproductive choices. They can pursue assisted reproductive techniques such as in vitro fertilization (IVF) while simultaneously minimizing the risk of passing on PKD to their offspring. Improved Pregnancy Outcomes: By selecting embryos that are free of the PKD gene mutation, couples increase the likelihood of having a healthy pregnancy and a child free of the disease. It can lead to improved pregnancy outcomes and the birth of healthy children. Overall, preimplantation diagnosis offers hope and empowerment to couples affected by PKD by providing them with the means to build a family while minimizing the risk of passing the disease to next generations.